Friday

August 1, 2014

August 1, 2014

Posted by **elle** on Saturday, January 27, 2007 at 9:28pm.

Find A and B such that

x-11/(x+3)(2x-1)= A/x+3 + B/2x-1

Multiply both sides by (x+3)(2x-1) to get rid of the fractions.

We end up with this:

(x-11) = A(2x-1) + B(x+3)

You can solve for A and B more easily now.

I hope this helps and is what the problem was asking.

how can estimation help you deside if the exact product for 7 times $74.65 is greater or less than $600?

**Related Questions**

Maths - Can you please help explain how to get the answer to 3/x = 2/5 thanks a ...

Math - I need help multiplying the fractions out. The question is... x/3 + y/2...

help please - What is the first step in solving the problem, 3x-8/12=9? A) Add 8...

PLEASE HELP ME!!! - What is the first step in solving the problem, 3x-8/12=9? A...

HELP!!!!! - What is the first step in solving the problem, 3x-8/12=9? A) Add 8 ...

please help math - x/3-2/3=1/x *Solve the rational below. I really need help. ...

Math - A=1/2H(B+b) Solve for H Let's start by getting rid of the fraction. ...

Algebra 1-Fractions - Or, eliminating fractions, I should say. So, I need some ...

Algebra - 89. Solve for x in the equation: 6/7x - 6 = -2 I posted this before, ...

math - Prove this identity (cos è - 1) / (cos^2 è) = sec è - sec^2 è I have a ...